Association of grade of non-alcoholic fatty liver disease and glycated albumin to glycated hemoglobin ratio in patients with type 2 diabetes mellitus. (March 2017) - Jung, Chan-Hee; Lee, Bora; Choi, Dug-Hyun; Jung, Sang-Hee; Kim, Bo-Yeon; Kim, Chul-Hee; Kang, Sung-Koo; Mok, Ji-Oh
Highlights: Relationship of GA/HbA1c ratio and grade of NAFLD by ultrasonography has not been evaluated in patients with T2DM. GA/HbA1c ratio significantly decreased across increasing NAFLD stages. There was no significant difference in HbA1c level among group of NAFLD stages. Lowest GA/HbA1c ratio tertile was significantly associated with the presence and severity of NAFLD on US. Abstract: Aims: The aim of this study was to investigate the association between the glycated albumin (GA) to glycated hemoglobin (HbA1c) (GA/HbA1c) ratio and grade of non-alcoholic fatty liver disease (NAFLD) on ultrasonography (US) in patients with type 2 diabetes mellitus (T2DM). Methods: This retrospective, cross-sectional study was performed with data obtained from 186 T2DM patients. Participants were assessed for serum GA/HbA1c ratio and fatty liver using US. NAFLD was defined as ultrasonographically detected fatty liver and was graded as normal, mild, moderate, and severe fatty liver. Results: A total of 98 subjects (53%) were diagnosed with NAFLD on US, of which 47 (48%) had moderate-to-severe grade of NAFLD. The mean GA level and GA/HbA1c ratio significantly decreased across increasing NAFLD stages (34% vs. 29% vs. 27% vs. 28%, p  = 0.023 for trend; 3.1 vs. 2.9 vs. 2.6 vs. 2.7, p  = 0.001 for trend, respectively), whereas there was no significant difference in HbA1c level among groups ( p  = 0.714 for trend). There was a significant decrease in prevalence of NAFLD across GA/HbA1c ratio tertiles (67% vs. 58% vs. 41%, p for trend = 0.007). Multivariate logistic regression analysis showed that individuals with the lowest GA/HbA1c ratio had an odds ratio (OR) of 2.75 (95% CI = 1.06–7.13) for having any grade of NAFLD and an OR of 4.48 [1.20–16.74] for moderate-to-severe grade NAFLD compared with the highest GA/HbA1c ratio even after adjustment for confounding factors ( p  = 0.038, p  = 0.026, respectively). Conclusion: The present study showed that GA/HbA1c ratio was significantly inversely associated with the presence and severity of NAFLD on US.